EKSISTENSIALISME DALAM SENI LUKIS SIMBOLISME (IKAN KOKI) - Kusdiana, Hilman Cahya (ATRAT: Jurnal Seni Rupa, 2022)
Freedom is an idea that is embodied in works of art or symbolism painting with media outside the convention of painting (canvas and paper). Freedom is symbolized by goldfish as a result of the interpretation of the relevance between individual freedom and cheffish. The artwork created utilizes guitars and fiddles as a medium to paint a goldfish with a symbolism approach. The concept of freedom is the result of observations and comparisons between the concept of freedom in the anime One Piece story, the philosophy of freedom and personal experience as an individual. This work refers to Kierkegard’s theory of existentialism, namely the highest freedom is to merge with God. In the end it was concluded that freedom is sincerity.Keywords: Kierkegard existentialism, Freedom is sincerity, Symbolism Painting, Chef fish, guitar and fiddle media----------------------------------------------------------------------------------Kebebasan adalah gagasan yang diwjuudkan dalam karya seni rupa atau seni lukis simbolisme dengan media di luar konvensi melukis (kanvas dan kertas). Kebebasan disimbolkan dengan ikan koki sebagai hasil interpretasi tentang relevansi antara kebebasan individu dan ikan koki. Karya seni yang diciptakan memanfaatkan gitar dan rebab sebagai media untuk melukis ikan koki dengan pendekatan simbolisme. Konsep kebebasan adalah hasil pengamatan dan perbandingan antara konsep kebebasan dalam cerita anime one piece, filsafat kebebasan dan pengalaman pribadi sebagai individu. Karya ini merujuk pada teori eksistensialisme kierkegard, yaitu kebebasan paling tinggi adalah meleburkan diri dengan Tuhan. Pada akhirnya disimpulkan bahwa kebebasan adalah keikhlasan.Kata Kunci: eksistensialisme Kierkegard, Kebebasan adalah keikhlasan, Seni Lukis simbolisme, Ikan koki, media gitar dan rebab